Future perspectives on international criminal justice - Stahn, Carsten, 1971-; Herik, L. J. van den (Larissa J.); Dugard, John, 1936- (The Hague, Netherlands : T.M.C. Asser Press, 2010)
"International criminal law is shaped by the influence of individual scholars and the impact of specific rulings and legal frameworks. This volume provides a fresh perspective on core themes and notions of international criminal justice. It revisits the sources, treatment and reception of doctrine and jurisprudence from an inter-generational perspective. It analyses the role of scholars and practitioners such as Arendt, Damaska and Cassese concerning the conceptualisation of law and jurisprudence. Then, it assesses the goals and scope of international criminal law, including contemporary developments relating to the interaction between international and domestic jurisdiction (e.g., verticality, complementarity, gravity), the role of actors (such as state crime, corporations, private military companies) and crime definitions (aggression, child recruitment). Finally, the book includes a review of key concepts and challenges of individual responsibility and international criminal procedure." "The volume is designed to provide a critical rethinking of existing law and practice. It includes contributions by established scholars and new voices, thus making the work relevant for academics, international and domestic courts and tribunals, as well as non-governmental organizations. It was produced within the framework of the Marie Curie Project of the Grotius Centre for International Legal Studies, Leiden University & Campus The Hague."--Jacket.
Introduction : Future perspectives on international criminal justice : through the looking glass / Carsten Stahn & Larissa van den Herik -- 'Satires of circumstance' : some notes on war crimes trials and irony / Gerry Simpson -- The banality of evil on trial / Alette Smeulers & Wouter Werner -- r Universal jurisdiction and the prosecution of excluded asylum seekers / Elizabeth Santalla -- The Inter-American Court of Human Rights and aggravated state responsibility : operationalizing the concept of state crime / Scott Doucet -- Corporations as future subjects of the International Criminal Court : an exploration of the counterarguments and consequences / Larissa van den Herik -- Grey war zone? : the question of contractual control of the privatization of warfare and the civilianization of the military / Dan Kuwali -- Holding private military corporations accountable for their crimes : the applicability of the commander/superior responsibility doctrine to crimes of PMCs / Materneau Chrispin -- Defining the crime of aggression / Astrid Reisinger -- Complementarity and aggression : a ticking time bomb? / Nicolaos Strapatsas -- The recruitment and use of child soldiers : some reflections on the prosecution of a new war crime / Michael E. Kurth -- The difficulty with individual criminal responsibility in international criminal law / Gideon Boas -- Current trends on modes of liability for genocide, crimes against humanity and war crimes / t Witness memory and the manufacture of evidence at the international criminal tribunals / Alexander Zahar -- Remedies for war victims / Liesbeth Zegveld -- Victim participation in ICC proceedings / Nino Tsereteli -- Arrest and surrender under the ICC statue : a contextual reading / Carsten Stahn.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- International cooperation; International crimes; International criminal courts; Droit international penal; Tribunaux penaux internationaux; Droit penal international; Jurisprudence internationale; Tribunaux penaux internationaux; Cour penale internationale; Criminal justice, Administration of -- International cooperation; International crimes; International criminal courts